Comparison of Revolving Scarf Osteotomy and Double Metatarsal Osteotomy for Treating Severe Hallux Valgus with an Increased Distal Metatarsal Articular Angle - Xinwen Wang; Liang Xiaojun MD (Foot & Ankle Orthopaedics, 2022)
Category: Midfoot/Forefoot Introduction/Purpose: The aim of this study was to introduce a new surgical procedure defined as revolving scarf osteotomy (RSO) and compare the clinical and radiological results of RSO and double metatarsal osteotomy (DMO) performed for treating severe hallux valgus (HV) with an increased distal metatarsal articular angle (DMAA). Methods: First metatarsal osteotomies were performed in 56 patients (62 feet) with severe HV with an increased DMAA in Honghui Hospital from January 2015 to December 2017. RSO was performed in 32 feet and DMO was performed in 30 feet. Clinical assessments were performed using the American Orthopaedic Foot & Ankle Society (AOFAS) score and visual analog scale (VAS) score. Radiographic evaluations of the hallux valgus angle (HVA), intermetatarsal angle (IMA), DMAA, and first metatarsal length (FML) were compared preoperatively and postoperatively in the two groups, and the rates of complications were also compared. Results: The mean AOFAS score, VAS score, HVA, IMA, and DMAA showed significant improvements in both groups after surgery, but with no significant differences between the two groups. The postoperative FML was significantly larger in the RSO group than in the DMO group (p<0.001). One of the 30 feet (3.3%) in the DMO group exhibited transfer metatarsalgia at 12 months postoperatively, while another foot (3.3%) in same group had avascular necrosis of the metatarsal head. One of the 30 feet (3.1%) in the RSO group had hallux varus. Conclusion: No differences in the clinical and radiographic results were observed between the two groups with severe HV and an increased DMAA. However, RSO may reduce postoperative complications compared to DMO. A long-term, randomized, controlled prospective study with a larger sample would provide higher-level evidence for confirming the clinical efficacy and safety of RSO.